Relevansi Perilaku Masyarakat Muslim Kota Semarang Dalam Mengupayakan Terwujudnya Kesehatan Reproduksi Perempuan Dengan Konsep Al Quran dan Al Hadis yang Sensitif Gender - Irawati, Retno Purnama; Kuswardono, Singgih (Jurnal Studi Agama dan Masyarakat, 2010)
Islam placed the position of the women in the high-ranking position and they are appreciated very well. There are many articles in the Qurâan that give and protect the womenâs rights. Interpretation on the Qurâanic articles and hadis is absolutely needed together with increasing problems in developing society. Â One of the problems that emerges is the problem of the rights of the womenâs reproduction. There is a gap between precepts in the Qurâan that guard and protect and promote the dignity of the woman in social lives and some practices in society especially among some Muslim scholars, intellectuals and common people, in which womenâs rights such as the right to choose a partner, the right to the sexual activity, the right to determine pregnancy including the determination of the distance of pregnancy, denying pregnancy, the use of contraception and abortion, the right to the children rearing, are still dominated by men that play a big role as a decision maker. This research explains the picture of the real situation. This research studies misunderstanding the Semarang city community towards the Qurâanic conception on womenâs rights. Qurâanic precepts actually have gender sensitivity about womenâs health and womenâs reproduction rights. This study found that 43.16% of the community misunderstands in interpreting Qurâanic precepts on womenâs health, and 37.87% ignoring womenâs right to choose their partner, while 48.14% has a gender-biased perception on the right on women to a sexual activity. Moreover, The Semarang community also has misperception on womenâs right to determine pregnancy, which reaches 43.37%, the same percentage as misperception on womenâs rights to children upbringing.Â